1969
DOI: 10.1172/jci106102
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol balance and fecal neutral steroid and bile acid excretion in normal men fed dietary fats of different fatty acid composition

Abstract: A B S T R A C T Six normal men were fed formula diets containing either highly saturated fat (cocoa butter, iodine value 32) or polyunsaturated fat (corn oil, iodine value 125). The sterol balance technique was used to compare the changes in serum cholesterol concentration with the excretion of fecal steroids. The method used for the analysis of fecal steroids was chemical, with a final identification and quantification by gas-liquid chromatography. It was confirmed that the chemical method for fecal steroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

1972
1972
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(84 citation statements)
references
References 29 publications
4
78
2
Order By: Relevance
“…24 Cholesterol synthesis measured by the sterol balance technique (Table 4) was also found to be 30% of normal production. 25 These results are in agreement with those reported by Salen et al, 26 Miettinen, 4 and Lin and coworkers. 10 According to Nguyen and colleagues, 15 the low cholesterol synthesis in sitosterolemic patients is associated with a markedly reduced microsomal hydroxymethyl glutaryl-coenzyme A (HMG-CoA) reductase activity, the rate-controlling enzyme for cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 92%
“…24 Cholesterol synthesis measured by the sterol balance technique (Table 4) was also found to be 30% of normal production. 25 These results are in agreement with those reported by Salen et al, 26 Miettinen, 4 and Lin and coworkers. 10 According to Nguyen and colleagues, 15 the low cholesterol synthesis in sitosterolemic patients is associated with a markedly reduced microsomal hydroxymethyl glutaryl-coenzyme A (HMG-CoA) reductase activity, the rate-controlling enzyme for cholesterol biosynthesis.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in eight of these studies, 44 " 51 the P/S ratio of the polyunsaturated diet averaged about 7-fold higher than that of the saturated diet (1.5 vs 0.2), and these studies reported an average decrease in plasma cholesterol levels of only 8%. In six other studies, 31 ' 39 " 13 the P/S ratio of the polyunsaturated diet averaged 27-fold higher than that of the saturated diet (4.6 vs 0.17), and this difference was associated with an average cholesterol decrease of 20%.…”
Section: Plasma Cholesterolmentioning
confidence: 89%
“…Sterol balance studies have been performed to evaluate the effects of the composition of the diet on sterol excretion (Connor et al, 1969;Grundy and Ahrens, 1969;Nestel et al, 1975). These metabolic ward investigations were elaborate, but owing to variations in bacterial degradation of the sterol ring structure in the large intestine, and variations in colonic transit time, precision was insufficient to settle the question of the effects of different diets on sterol excretion (Andersson and Bosaeus, 1993).…”
Section: Introductionmentioning
confidence: 99%